Effects of medium- and long-distance running on cardiac damage markers in amateur runners: a systematic review, meta-analysis, and metaregression - Jacobo Á. Rubio-Arias; Luis Andreu; Luis Manuel Martínez-Aranda; Alejandro Martínez-Rodríguez; Pedro Manonelles; Domingo J. Ramos-Campo (Elsevier, 2021)
Background: To finish an endurance race, athletes perform a vigorous effort that induces the release of cardiac damage markers. There are several factors that can affect the total number of these markers, so the aim of this review was to analyze the effect of endurance running races on cardiac damage markers and to identify the factors that modify the levels of segregation of these cardiac damage markers. Methods: A systematic search of PubMed, Web of Science, and the Cochrane Library databases was performed. This analysis included studies where the acute effects of running races on cardiac damage markers (troponin I and troponin T) were analyzed, assessing the levels of these markers before and after the races. Results: The effects of running races on troponin I (mean difference = 0.0381 ng/mL) and troponin T (mean difference = 0.0256 ng/mL) levels were significant. The ages (R2 = 14.4%, p = 0.033) and body mass indexes (R2 = 14.5%, p = 0.045) of the athletes had a significant interaction with troponin I. In addition, gender, mean speed, time to finish the race, and type of race can affect the level of cardiac damage markers. Conclusion: Endurance running races induce the release of cardiac-damage markers that remain elevated for at least 24 h after the races. In addition, young male athletes with high body mass indexes who perform races combining long duration and moderate intensity (i.e., marathons) release the highest levels of cardiac damage markers. Physicians should take into consideration these results in the diagnosis and treatment of patients admitted to the hospital days after finishing endurance running races.